A Critique on the Book Ressentiment - Ali Yaghoobi Choobari; Hamideh Mohammadzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to review and critique one of the most important books of Max Scheller called Ressentiment. This research has been done by the descriptive-analytical method. In this book, Scheller introduces ressentiment as well as Nietzsche's view of the issue, which he, under the influence of this famous German philosopher, introduced and expanded the ressentiment concept. According to Max Scheller, the modern world and modernity, wherever it expands, creates a kind of emotional structure where he calls this emotional construction ressentiment. According to him, this feeling appears when the social actor wants to change a social situation, but is not able to do so. The results of the critique and review of this book show that this book, despite some strengths such as notes section, index of subjects, and index of persons at the end of the book provides more information to the reader about the content of the book, it has many defects in the field of form and content, unfortunately. Some of these include lack of footnotes of German and English terms, proper nouns, the lack of a glossary at the end of the book, the existence of typographical errors, use of inaccurate equivalents, and inconsistent use of equivalents.